SYSTEMATIC REVIEW PENGARUH INTENSITAS CAHAYA TERHADAP KELELAHAN MATA PEKERJA - Adinda Pramesthi Riadyani; Chahya Kharin Herbawani (Jurnal Kesehatan Masyarakat (Undip), 2022)
Lighting is an important physical environmental factors in working. Poor lighting can cause eye fatigue and even cause eye damage. This study aims to analyze the effect of light intensity on eye fatigue on workers. The research was using a systematic review method with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) and the search results obtained 74 articles and only 7 articles that met the inclusion criteria. The results obtained are eye fatigue can be influenced by several factors, including age, length of work, eye health history, and light intensity. It was found that many work environments from various fields still have poor light intensity (below the standard) that caused eye fatigue complaints in most of the workers in the area, which is also influenced by other factors. In conclusion, there is a significant effect of light intensity on eye fatigue on workers either directly or indirectly. Due to the time difference between the research articles with the same hypothesis, this is an important issue that needs to be considered by the company so that occupational diseases do not occur due to an unsafe work environment.